The P25 component of Galleria silk - Zurovec, M; Kodrík, D; Yang, C; Sehnal, F; Scheller, K (Molecular & general genetics, 1998)
The water-insoluble core of lepidopteran silk is composed of four major proteins, but only three genes have been identified. This study demonstrates that the 29- and 30-kDa components of Galleria mellonella silk are derived from a single gene designated P25. The gene is expressed exclusively in the posterior section of the silk glands as a 2-kb mRNA, which accumulates in the feeding larvae and declines at molting. The mRNA encodes a peptide of 24,864 Da that exhibits 51% identity with the putative product of the P25 gene of Bombyx. The conservation of several amino acid stretches, including the relative positions of all 8 cysteines in the mature polypeptide, implies that the P25 proteins play similar, and apparently significant roles in silk formation in the two species. A Galleria P25 cDNA yields a peptide of about 25 kDa when translated in vitro; the 29- and 30-kDa forms present in the silk are derived from this primary translation product by differential glycosylation.
Keywords: Fibroins; Glycoproteins; Molecular Sequence Data; sekvence aminokyselin; Genes, Insect; Sequence Alignment; hmyzí geny; bourec; Lepidoptera; Bombyx; Base Sequence; sekvence nukleotidů; zvířata; Amino Acid Sequence; hmyzí proteiny; fibroiny; northern blotting; molekulární sekvence - údaje; glykoproteiny; sekvenční homologie aminokyselin; Blotting, Northern; Insect Proteins; sekvenční seřazení; Sequence Homology, Amino Acid; Animals